Nursing home care in Brasil and the World: a historical and ethical view - Taka Oguisso (Cultura de los Cuidados, 2012)
The origins of home care are described, as well as its definitions and objectives according to the World Health Oganisation, and the way it is developed in some countries in which the system has been implemented with a new modality involving less professional training, by means of carers or comforters, in order to ensure people's comfort, especially that of the elderly at home. Home nursing care delivered in Brazil by nurses employed for this purpose is described as an example, as well as the ethical and legal issues that may arise. In European countries there are certain specific requirements such as previous hospital experience and specialised training in public health and/or obstetric nursing, for nurses to deliver home care, which is understandable considering the legal and technical responsibilities for the nurse who will be alone in the home with no one else to discuss decisions with.